Public Open Space as Urban Architecture: Design and Public Life - Nasution, Achmad Delianur; Zahrah, Wahyuni (Institut Teknologi Sepuluh Nopember, 2017)
Public open space (POS) does not become an adequate priority in urban planning and design in developing countries, including Indonesia. The cities are almost ‘full of buildings’ and ‘less of POS.' Meanwhile, many studies show that the POS has a significant effect on citizens’ quality of life. By this situation, the research means to explore the quality of public open space in relation to its utilization. The study observed POS in several small towns in North Sumatra Province, where new urbanized area had been rising by autonomy regulation. A visual survey was carried out to record, map and identify the quality of the public open spaces. Besides, the visitors were interviewed to get their perception of the quality of POS. The investigation indicates that almost of public life did not always equal with the design of the POS. Almost POS have no pedestrian linkage to make it connect with the other urban space. Thus, the majority of POS was alienated with the other part of cities.There was no integration with public transport, too. The facilities were less of maintenance. However, the community kept coming to the place and doing many activities. The respondents perceived the POS as quite good, but not good enough. Still, they mostly believed that the POS have a real impact on their quality of life.